Babs Padelford letter to Thomas H. Kent regarding field notes, June 3, 1982 - Padelford, Babset al (1982)
Field notes were contributed by Babs Padelford in a letter to Thomas H. Kent. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed/flatbed